Face strategies and intertextuality in statements of ordinary witnesses in two criminal trials in Santiago, Chile - Infante Arriagada, Pascuala (Lenguas Modernas, 2024)
The criminal trial is characterized by a clear manifestation of face strategies that witnesses try to deploy orally, as well as by the organized circulation of texts (both oral and written) that interact in rigidly pre-established routines. Through the analysis of the statements of ten ordinary witnesses in two trials, this article examines the valorizing and de-valorizing strategies most typically used by witnesses, as well as the relationship of these strategies with two types of intertextuality exploited by lawyers: that codified in Article 332 of the Chilean Criminal Procedure Code, and that which is elicited through direct and indirect reported speech. Results indicate that lawyers resort to intertextuality especially for discrediting the (narrative of the) witnesses, which in turn determines more markedly strategic behaviors in the witnesses’ responses. Likewise, the study identifies a tendency for witnesses to prioritize their individual face presentation, even to the detriment of the accused or victim on whose behalf they testify.